A case of multiple self-inflicted cuts to the neck and wrist presenting with airway compromise and catastrophic hemorrhage - Mani, Utsav Anand; Bhot, Firdaus Behram; Sada, Elizabeth; Mishra, Prasun; Patil, Vishwanath; Ursekar, Rajesh; Adake, Digvijay; Shriyan, Sushma (Indian Journal of Case Reports, 2019)
Cut-throat injuries are seen commonly, however, the reporting in the medical literature is not so common. Due to the close proximity of the vital structures in the neck, there is a high risk of compromise to the airway. Transection of just the ulnar artery in itself is sufficient to cause death within a period of 6 hours. Here, we report the case of a 22-year-old male patient with a history of a self-inflicted wound on the anterior aspect of the neck which was associated with bleeding and respiratory distress and multiple incised wounds over the left wrist. The patient was then taken up in the OT for wound exploration and suturing by an ENT surgeon. Simultaneously Radial and Ulnar artery repair, with the repair of multiple flexor tendons of the left forearm was done by a vascular surgeon and a plastic surgeon, respectively.